Knowledge of mothers regarding children’s vaccinations in Greece: an online cross-sectional study - Giannakou, Konstantinos; Kyprianidou, Maria; Hadjikou, Andria; Fakonti, Georgia; Photiou, Galatia; Tzira, Eleana; Heraclides, Alexandros (My University, 2021)
Background: One of the main reasons that influence parental choice to postpone or avoid children’s vaccination is insufficient knowledge. Mothers’ knowledge can be considered as an important factor when determining childcare, as they are often the primary decision maker for their children’s healthcare issues. This study aimed to assess the level of mothers’ knowledge and practice on certain aspects of vaccination for their child/children in Greece. Methods: This was an online cross-sectional survey, which collected information about mother’s socio-demographic characteristics, vaccination-related information, and vaccine knowledge using a self-administered questionnaire. The survey was conducted between April 2020 and June 2020 and the study population included mothers over 18 years old with at least one child (< 18 years old), living in four broad geographical areas of Greece (Attica, Central Greece, North Greece, and Crete/Aegean Islands). Results: A total of 1885 Greek mothers participated in the study. The majority stated that they vaccined their child/children (98%), and the most popular source of information about vaccination was their child’s pediatrician (89%). About half of participants (52%) have delayed their child/children vaccination with their pediatrician’s suggestion being the main driver. The median knowledge score was 11 which indicates a high knowledge level for childhood vaccination among Greek mothers. Multiple linear regression analysis identified an inverse association between education and knowledge score, characterized by higher knowledge scores among individuals with secondary and even higher among those with higher education. Multiple logistic regression analysis showed that the strict adherence to the prescribed dosage as indicated by the local recommendations for each vaccine, was associated with most of the knowledge items included in the study. Conclusions: Our findings show that the vast majority of mothers in Greece did vaccinate their child/children, while pediatricians appear to have a very influential role in mothers’ decision making. High knowledge around vaccination was associated with mothers’ educational attainment, being particularly high among those who completed higher education. Considerable attention is required from public health authorities to promote vaccination through educational programs and campaigns, particularly aimed at people with lower educational attainment. Additionally, improving communication between pediatricians and mothers to reach those women who have not decided to vaccinate or delayed vaccination for their children, may prove to be very beneficial.
Keywords: Children; Greece; Immunization; Knowledge; Mothers; Vaccination